"Agora eu decido meus horários de trabalho”: um estudo ergológico da atividade de profissionais teletrabalhadores de um órgão público do poder judiciário - Anchieta, Rebeca Boreli de (2019)
The present study focused on work situations in the activity of teleworkers, more specifically technicians and judicial analysts, of a Court located in the city of Vitória-ES. The research problem that guides this study is the following question: How do the servants face the situations experienced in the telework of a public organization of the judiciary? The objective was to analyze, in the light of Ergology, the management aspects in the activity of telecommuting public servants, besides observing, describing and discussing the real work situations and the uses of themselves when they are teleworking. To achieve the proposed objective, a theoretical framework was first presented about the context that gave rise to and the main concepts of teleworking. Then it was presented about the theoretical lens used in this study than Ergology. The production of data was based on a qualitative investigation, whose first step was to consult Resolution CNJ 227/2016, which regulates teleworking within the scope of the judiciary, as well as other information obtained from the agency's own website. The second stage was a semi-structured and individual interview with 10 teleworkers, and the third and last was the direct observation of two days of face-to-face work and one day of teleworking by a server. Data analysis was performed through content analysis of interviews and direct observation, which allowed to separate into four categories of analysis that were defined a posteriori, as follows: a) the dramatic of being a civil servant and teleworker; b) the fragile boundaries of time and space in the activities of a teleworker; and c) Telework and the collective work. It was possible to notice a strong influence of individual values that led the servers to choose to be public servants and do teleworking. It was also noted the uses of self and renormalization in the face of teleworking situations in which there is no clear delimitation of time and space of workplace and home. In addition, we discussed the consequences of teleworking in relation to the collective work. It is believed that this study may contribute to the clarification of the work situations experienced by teleworkers and their successive uses of themselves and renormalizations that now have work at home.